Occurrence of disulfoton residues in coffee leaves following a soil application of the insecticide - Rigitano, Renê Luís de O.; de Souza, Júlio César (Pesquisa Agropecuaria Brasileira, 1994)
The accumulation of disulfoton residues in coffee (Coffea arabica L. cv. 'Catuaí' Vermelho) leaves was investigated following a soil application of a granular formulation of the insecticide (Solvirex 10G) in field plots of 'Catuaí' coffee located in Lavras and in Patrocínio, MG, Brazil. The control of the coffee leaf miner (Perileucoptera coffeella), the most important insect pest of coffee in Minas Gerais, was also evaluated. The insecticide was applied at the beginning of the rainy season (early November) at the rates of 25 and 50 g of the formulation per tree. Samples of leaves were collected at fifteen-day intervals and the residues of disulfoton and its toxic oxidation products were determined by liquid-gas chromatography using a flame photometric detector. Maximum rates of residues were found in the leaves in the 3.9 and 9.3 ppm concentrations about the end of January in Patrocínio, and in the 6.9 and 17.7 ppm concentrations in Lavras for the 25 and 50 g/tree, respectively. In Patrocínio, where the infestation was higher, the application of 50 g/tree resulted in a control of the leaf miner up to the end of May, when the residues levels decreased to about 2 ppm.
Keywords: rainy season; Perileucoptera coffeella; leaf miner; 'Catuaí' coffee; chromatography